(x-3)2+(y+7)2=9

Simple and best practice solution for (x-3)2+(y+7)2=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)2+(y+7)2=9 equation:


Simplifying
(x + -3) * 2 + (y + 7) * 2 = 9

Reorder the terms:
(-3 + x) * 2 + (y + 7) * 2 = 9

Reorder the terms for easier multiplication:
2(-3 + x) + (y + 7) * 2 = 9
(-3 * 2 + x * 2) + (y + 7) * 2 = 9
(-6 + 2x) + (y + 7) * 2 = 9

Reorder the terms:
-6 + 2x + (7 + y) * 2 = 9

Reorder the terms for easier multiplication:
-6 + 2x + 2(7 + y) = 9
-6 + 2x + (7 * 2 + y * 2) = 9
-6 + 2x + (14 + 2y) = 9

Reorder the terms:
-6 + 14 + 2x + 2y = 9

Combine like terms: -6 + 14 = 8
8 + 2x + 2y = 9

Solving
8 + 2x + 2y = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + 2x + -8 + 2y = 9 + -8

Reorder the terms:
8 + -8 + 2x + 2y = 9 + -8

Combine like terms: 8 + -8 = 0
0 + 2x + 2y = 9 + -8
2x + 2y = 9 + -8

Combine like terms: 9 + -8 = 1
2x + 2y = 1

Add '-2y' to each side of the equation.
2x + 2y + -2y = 1 + -2y

Combine like terms: 2y + -2y = 0
2x + 0 = 1 + -2y
2x = 1 + -2y

Divide each side by '2'.
x = 0.5 + -1y

Simplifying
x = 0.5 + -1y

See similar equations:

| -4v+6-8=-38 | | p=2x+5+4x-3+1n | | G+9=6(g-11) | | 4(5k+3)+3(-4k-4)=-48 | | 8a+4=4a | | 27=4p+3r | | k^2-13k+37=-5 | | 5b-b-3b+1=20 | | B+4b-22=7b | | -5x^2+400x-2550=0 | | ln(x^5/x^3) | | H=6x(40-x) | | 16x^9-9x^7+20x^6= | | 18/3=x/4 | | 18/3=x/$ | | 2(w-7)=3w | | 14p+(-11p)-(-14)=2 | | p(x)=x^3+7x^2+17x-25 | | H=6t(40-t) | | 12k=-6(k+9) | | 5-(3x-6)= | | 6f+30+8=2f | | 22/24 | | 2x+4y+2=5 | | 5x-12=-7x | | 10+12y=2y-40 | | -r-(-9r)-20=-4 | | 2(x-1)-6x=26 | | 15/30 | | 19h-9h-9h+2=18 | | 25+30.76=3+5 | | 20-x=4x+5 |

Equations solver categories